SeDiCI - Desafíos y experiencias en la vida de un repositorio digital - De Giusti, Marisa Raquel (2011)
The Intellectual Creation Dissemination Service is the Institutional Digital Repository of La Plata National University.\nThe project is intended to be the main distribution source of all the academic work produced inside UNLP. In view of main worldwide institutions's trend towards the publication of academic resources through open access digital repositories, SeDiCI has pointed to become a strategic tool to bring relevance to the University.\nSince its creation in the year 2003, SeDiCI has faced up many challenges and difficulties. Thus the initiative has been directly and indirectly affected during its development and growth.\nDespite these difficulties, SeDiCI hosts nowadays more than 14000 academic resources produced in the UNLP, which are freely accessible via a web portal. SeDiCI is currently one of the most important digital repositories at the national and regional (Latin America) level.\nThis work presents many of the experiencies and challenges that have shaped up SeDiCi, describing problems, context and solution approaches. Topics include the need for institutional support, many cataloguing issues, ways to improve services to users, resource digesting (import), among others. This document also describes some of the new and most recent challenges and the current research and development trends, which are oriented to improve and extend the services provided by SeDiCI (harvesting tools, text analysis tools, ontologies and semantic repositories, open access legislation, DSI, Self-archiving, and many others). The purpose of this document is to share the lived experiences with this project, which may be useful to other institutions working on their own digital repositories.